Modeling of the adaptive system of individualization and personalization of future specialists’ professional training in the conditions of blended learning (Educational Dimension, 2021)
The model of adaptive system of individualization and personalization of future specialists’ professional training in the conditions of blended learning is offered. It includes the contextual, pedagogical and instrumental subsystems. In the system, the adaptability is planned to be implemented through the adaptation of educational materials, monitoring, devices, face-to-face classes; individualization involves the study of students’ individual features, support and assistance of student’s individual syllabus, individualization of the learning process, development of student’s individual features and formation of new characteristics according to student’s educational needs, monitoring of student’s individual progress; personalization involves the organization of the educational environment, including the electronic one.
Keywords: model of adaptive system